The Morphology and Significance of Some Imāmī Shī‘ite Traditions - Buckley, R. P. (Journal of Semitic studies, 2007)
The article seeks to explore a corpus of Imāmī Hadīth featuring an encounter between the Shī‘ite Imām Ja‘far al-Ṣādiq (d. 765 AD) and the Abbasid caliph al-Manṣūr (r. 754.75). It does this by employing the methods of structural analysis initially devised by Vladimir Propp in his Morphology of the Folktale (1928) and further developed by later anthropologists and folklorists such as Alan Dundes. The article identifies the repertoire of motifs from which the traditions are composed and studies these in terms of their functional equivalence within the narratives. The wider thematic structure of the traditions is also investigated and is found to provide insights into the cultural significance of the corpus as an articulation of the Imāmī Shī‘ite view of the relationship between religious and political authority.